2010
DOI: 10.1002/eqe.976
|View full text |Cite
|
Sign up to set email alerts
|

Soil–structure interaction effects observed in the in situ forced vibration and pushover tests of school buildings in Taiwan and their modeling considering the foundation flexibility

Abstract: In the conventional structural seismic analysis, the rigid base model is usually adopted without considering the flexibility of the ground, leading to inaccurate estimation of the vibration characteristics and the seismic response of the structure. In 2007, several in situ tests were conducted by the National Center for Research on Earthquake Engineering (NCREE) on the school buildings in the Guanmiao Elementary School in Tainan, Taiwan. For the study of soil–structure interaction (SSI) effects, the forced vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Michel et al (2011) quantified and modeled the relative frequency decay and damping variation of low-rise modern masonry buildings in order to bring an analytical method to encompass the basic frequency, in which they argued that the SSI phenomenon should also be accounted for. After examining and comparing the experimental results obtained by forced-vibration tests and that by finite-element analyses on a school building in Taiwan, Ko and Chen (2009) found that the flexibility of foundation had a considerable impact on the results of structural analysis. Trifunac et al (2010) conducted a comprehensive study on the response of a 14-story reinforced concrete building in Srpska to 20-recorded earthquakes, and they found that essentially linear SSI was observed in these recorded data.…”
Section: Introductionmentioning
confidence: 99%
“…Michel et al (2011) quantified and modeled the relative frequency decay and damping variation of low-rise modern masonry buildings in order to bring an analytical method to encompass the basic frequency, in which they argued that the SSI phenomenon should also be accounted for. After examining and comparing the experimental results obtained by forced-vibration tests and that by finite-element analyses on a school building in Taiwan, Ko and Chen (2009) found that the flexibility of foundation had a considerable impact on the results of structural analysis. Trifunac et al (2010) conducted a comprehensive study on the response of a 14-story reinforced concrete building in Srpska to 20-recorded earthquakes, and they found that essentially linear SSI was observed in these recorded data.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to realize the actual behavior of a typical school building subjected to lateral loading, a series of in situ tests were executed by the National Center for Research on Earthquake Engineering [17][18][19][20]. Therefore, in order to realize the actual behavior of a typical school building subjected to lateral loading, a series of in situ tests were executed by the National Center for Research on Earthquake Engineering [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory tests, the size of a school building specimen is limited, and neither the qualities of materials nor construction can be mirrored exactly. Therefore, in order to realize the actual behavior of a typical school building subjected to lateral loading, a series of in situ tests were executed by the National Center for Research on Earthquake Engineering [17][18][19][20]. Besides the tests of the building without retrofit [17][18][19], the benefits of some retrofit methods were verified, including the addition of reinforced concrete (RC) wing walls, enlarging columns [20], and adding sandwich columns.…”
Section: Introductionmentioning
confidence: 99%
“…Eduardo K. provided a concise review of some of the leading developments of SSI (Eduardo et al, 2010). In 2007, several in situ tests and corresponding simulations using the finite element method were conducted for school buildings in Taiwan (Ko et al, 2010).…”
Section: Introductionmentioning
confidence: 99%